Radiofrequency ablation of hepatocellular carcinoma: CT texture analysis of the ablated area to predict local recurrence. Issue 150 (May 2022) - Beleù, Alessandro; Autelitano, Daniele; Geraci, Luca; Aluffi, Gregorio; Cardobi, Nicolò; De Robertis, Riccardo; Martone, Enrico; Conci, Simone; Ruzzenente, Andrea; D'Onofrio, Mirko
Abstract: Purpose: To investigate the role of CT-texture analysis of liver ablation area to predict local recurrence after HCC ablation. Methods: Patients treated with liver ablation were retrospectively enrolled. CT-texture analysis was performed on the core and borders of ablation area 1–2 months after procedure. Tumors were grouped according to the onset of local recurrence at follow-up (persistence, recurrence-free, short- or long-term recurrence). Differences in texture parameters and which parameters were predictive of recurrence risk were assessed using a Cox regression model. Results: 151 HCCs were treated in 98 patients (72 ± 9 years, 83 men). 68 HCCs reported no disease recurrence, 32 persistent disease, 19 short-term and 32 long-term recurrence. Median follow-up was 280 [IQR: 156–569] days. Venous phase (Ven)Skewness (HR 6.07, 1.29–28.6, p =.02) and VenKurtosis (HR 2.27, 1.23–4.21, p =.01) of the ablation core were predictive of short-term recurrence. VenHUmean (HR 0.30, 0.11–0.81, p =.02) and VenGLRLM_HGRE (HR 1.06, 1.01–1.11, p =.02) of the core were independent predictors of tumor recurrence (C-index 0.64, CI 0.52–0.76, p =.03). Arterial phase (Art)Entropy of ablation border predicted the recurrence risk (HR 3.15, 1.05–9.42, p =.04) and values higher than 3.71 reported an increased recurrence incidence (p =.05). ArtHUstd (HR 1.14, 1.04–1.24, p =.01), LateHUmean (HR 8.69, 1.11–68.23, p =.04), LateGLRLM_HGRE (HR 0.9, 0.82–0.99, p =.03), LateGLZLM_HGZE (HR 1.01, 1.00–1.02, p <.01) and LateGLZLM_SZHGE (HR 0.99, 0.99–1.00, p =.02) of ablation border were independent predictors of local recurrence risk (C-index 0.73, CI 0.61–0.86, p <.01). Conclusions: CT texture analysis of ablation area performed at 1–2 months follow-up could estimate the risk of local recurrence of hepatocellular carcinoma treated by radiofrequency ablation.